FRI0299 Pulmonary Arterial Hypertension in Idiopathic Inflammatory Myopathies: Data from The French Pulmonary Hypertension Registry and Review of The Literature. (15th July 2016) - Sanges, S.; Yelnik, C.; Sitbon, O.; Benveniste, O.; Mariampillai, K.; Phillips-Houlbracq, M.; Pison, C.; Deligny, C.; Inamo, J.; Cottin, V.; Mouthon, L.; Launay, D.; et al.
Abstract : Background: Occurrence of pulmonary arterial hypertension (PAH) in idiopathic inflammatory myopathies (IIM) without extensive interstitial lung disease (ILD) has been rarely described. Objectives: This study aimed to report all cases with association of PAH and IIM in the French Pulmonary Hypertension (PH) Registry, to identify IIM features associated with PAH, and to describe treatment modalities of these patients. Methods: All cases of IIM-PAH were retrieved from the French PH Registry, which gathers PAH patients prospectively enrolled by 21 referral centers across France. Patients were excluded if they had an extensive ILD or overlap syndrome. Characteristics of IIM-PAH patients were compared to a control group of IIM patients without PH. Results: Among the 5223 PAH patients in the Registry, 34 had a diagnosis of IIM. Among them, 3 IIM-PAH patients had no sign of extensive ILD or overlap syndrome, and were included in this study. In these patients, dermatomyositis (DM) was the only identified IIM. Two of them had a myopathic DM, confirmed by electromyography and biopsy. The last patient had an amyopathic DM, associated with anti-Ku antibodies. Pre-capillary PH was hemodynamically proven in all patients. PAH always developed after IIM onset, was severe in all cases, and led to a marked functional impairment. By pooling our cases with 6 previously reported patients, and comparing them to a control cohort of 35 IIM patients without PH, we identify several IIM characteristics possibly associated with PAH occurrence, including DM subtype (78% vs. 46%, p =0.02), skin involvement ( p =0.04), anti-SSA antibodies ( p =0.05) and peripheral microangiopathy ( p =0.06). Overall, IIM-PAH patients were managed by corticosteroids and/or immunosuppressants, either alone or combined with PAH therapy. Patients that did not receive PAH therapy did not seem to respond to IIM treatment alone. Conclusions: Our study reports for the first time the rare but possible association of PAH and IIM in a large prospective PH Registry. In that setting, PAH seems associated with DM, skin involvement, peripheral microangiopathy and anti-SSA positivity. The best therapeutic strategy for IIM-PAH remains to be defined. Disclosure of Interest: None declared